A MIMO Reversed Antenna Array Design for gsm1800/td-scdma/lte/wi-max/wiLan/wifi - Fang Xu; Mu Ju (International Journal of Antennas and Propagation)
A triband MIMO antenna used for gsm1800/td-scdma/lte/wi-max/wiLan/wifi has been proposed in this paper. The design with the size of 32 m ∗ 73.6 mm is fabricated on FR4 substrate (thickness is 1.6 mm). This antenna consists of two reversed monopole meandered radiators and defected ground structure which work together to achieve impedance match and enhance isolation for all operating bands. According to the subsequent measured results, the working frequency domains are at gsm1800 (1.71 GHz–1.88 GHz), td-scdma (1.88 GHz–2.025 GHz), lte (2.1–2.35, 2.48–2.51), wi-max (3.5 GHz, 5.5 GHz), wiLan (5.725 GHz–5.8 GHz), and wifi (5.8 GHz–5.88 GHz) approximately. Besides, the measured radiation patterns (gain total) are also well at these working frequency domains and the omnidirectional performance has been achieved for the reversed MIMO antenna array. Furthermore, the realized isolation is more than 15 dB, 24.2 dB, and 22 dB at the first, the second, and the third working frequency band, respectively.